Tolerance testing for cooked porridge made from a sorghum based fortified blended food - Chanadang, Sirichat (Kansas State University, 2015)
Products must be tolerant to many conditions, particularly when those products are prepared by consumers. Consumers may not measure added ingredients, they may add or leave out ingredients specified in recipes, or change cooking and holding times for foods. Fortified blended food (FBFs) are used as a source of nutrition for disaster or famine relief in developing countries and sorghum is looked at as a potential alternative to wheat and corn based products that are currently being used as FBFs. Porridge products are the most common dishes prepared from FBFs with a wide range of solids content, cooking times and variations in added ingredients such as sugar and fruit. This study was intended to evaluate the tolerance to preparation variations for a porridge product made as a FBF intended for food aid. Whole Sorghum Soy Blend (WSSB), a fortified, extruded, ground cooked cereal was selected as the FBF for this study. Descriptive sensory analysis was performed to evaluate the tolerance of porridge products made from variations in ingredients and cooking procedures. In this study, most sensory properties were only marginally affected by variations in ingredients or procedures. However, as expected, large differences occurred in some properties such as thickness when solids content varied or sweetness and fruit flavor when fruit was added. Tolerance testing showed that the sensory properties of WSSB had high tolerance to variations in cooking procedures, a positive aspect for product use and development. This means that the product can be modified during preparation by consumers without having a major impact on most sensory properties.
Keywords: Tolerance; Fortified blended foods (FBFs); Porridge; Sensory descriptive; Nutrition (0570)